Individual differences in good manners rather than compassion predict fair allocations of wealth in the dictator game - Zhao, Kun; Ferguson, Eamonn; Smillie, Luke D. (Wiley, 2016)
Objective. One of the most common tools for studying prosociality is the dictator game, in which allocations to one’s partner are often described in terms of altruism. However, there is less consensus regarding the motivations driving these allocations, which may represent either emotional concern for others (compassion), adherence to social norms regarding fairness (politeness), or both. Method. In this paper, we apply personality psychology to the study of behavior in the dictator game, in which we examine the discriminant validity of distinct prosocial constructs from the Big Five and HEXACO models in relation to allocations of wealth. Results. Across four studies (combined N = 798) utilizing both hypothetical and incentivized designs, we found that the politeness—but not compassion—aspect of Big Five agreeableness, as well as HEXACO honesty-humility, uniquely predicted dictator allocations within their respective personality models. Conclusions. These findings contribute to a growing literature indicating that the standard dictator game measures “good manners” or adherence to norms concerning fairness, rather than pure emotional concern or compassionate motives, which have important implications for how this paradigm is used and interpreted in psychological research.